Middle Ear Ceruminous Gland Adenoma Obstructing the Eustachian Tube Orifice - Jeong, Hamin; Noh, Haemin; Kim, Chang-Hee (Case Reports in Otolaryngology, 2021)
Ceruminous glands are located in the skin of the cartilaginous portion of the external auditory canal, and ceruminous gland adenoma originating from the middle ear mucosa is extremely rare. We report a case of middle ear ceruminous gland adenoma which caused long-standing otomastoiditis and mixed hearing loss with a large air-bone gap by obstructing the bony Eustachian tube. We discuss the clinical characteristics and histologic features of the present case.